A Study of Mathematical Problem Solving Ability and Reasoning Mathematical Ability on the Topic of Probability by Organizing Learning Activities using IMPROVE Method of Mathayomsuksa 3 Students - เรียบเรียง, วรรณิภา (RMUTI Journal Humanities and Social Sciences, 2018)
The objective of this research were 1) to compare the mathematical problem solving ability on the topic of probability of Mathayomsuksa 3 students between before and after learning by using the learning activities of IMPROVE method, 2) to compare the mathematical problem solving ability on the topic of probability of Mathayomsuksa 3 students after learning by using the learning activities of IMPROVE method with the 60 percent criterion, 3) to compare the reasoning mathematical ability on the topic of probability of Mathayomsuksa 3 students between before and after learning by using the learning activities of IMPROVE method, and 4) to compare the reasoning mathematical ability on the topic of probability of Mathayomsuksa 3 students after learning by using the learning activities of IMPROVE method with the 60 percent criterion. The sample was the Mathayomsuksa 3/4, in the 2nd semester of 2017 of Nonsungsritani school, Nonsung sub-district, Nonsung district, Nakhon Ratchasima Province, consisting of the 45 students which selected through purposive sampling technique. The research instruments were the learning organization plan of the probability for the Mathayomsuksa 3 students follow the IMPROVE method, total numbers of plans are 5, each plan used 2 periods, with 50 minutes per a period, and the instrument for collecting data was the essay test for mathematical problem solving and reasoning mathematical ability on the topic of probability of Mathayomsuksa 3 students, consisting of 8 items. The essay test for mathematical problem solving ability, the item diffi culty ranged between 0.23 - 0.48, the item discrimination ranged between 0.28 - 0.96, and the overall reliability was 0.89, and the essay test for reasoning mathematical ability, the item diffi culty ranged between 0.25 - 0.67, the item discrimination ranged between 0.28 - 1.00, and the overall reliability was 0.91. The collected data were analyzed using the percentage, the arithmetic means, the standard deviation, and the t-test statistics. The results were as follows: 1. The mathematical problem solving ability on the topic of probability of Mathayomsuksa 3 students, after learning is higher than before learning by using the learning activities of IMPROVE method, statistically signifi cant at the 0.05 level. 2. The mathematical problem solving ability on the topic of probability of Mathayomsuksa 3 students, after learning by using the learning activities of IMPROVE method is higher than with the 60 percent criterion, statistically signifi cant at the 0.05 level. 3. The reasoning mathematical ability on the topic of probability of Mathayomsuksa 3 students, after learning is higher than before learning by using the learning activities of IMPROVE method, statistically signifi cant at the 0.05 level. 4. The reasoning mathematical ability on the topic of probability of Mathayomsuksa 3 students, after learning by using the learning activities of IMPROVE method is higher than with the 60 percent criterion, statistically signifi cant at the 0.05 level.